(untitled) (Herald of the National Children’s Medical Center, 2024)
Intestinal intussusception in children refers to particular types of acquired intestinal obstruction, while in most cases it occurs in infants. This disease develops in infants against the background of anatomical and physiological features, which include mobility of the ileum and caecum, immaturity of the Bauginia flap.